The Development of Jumping Ability in Young Handball Players 12-13 Years Old - Sitorabonu Savriddin Qizi Abduyeva (Athena: Physical Education and Sports Journal, 2023)
To increase the level of jumping ability (high-speed strength abilities), a depth jump training program has been developed, taking into account technical and tactical actions in the game "Handball". Classes in the handball section are nothing more than a well-organized and well-thought-out system in which the qualitative and quantitative characteristics in the preparation of children correspond to both the general tasks of physical education and age-specific ones. Jumping like motor quality, refers to the speed-power abilities of a person. An indicator of a significant development of speed-strength training and, as a consequence, an increase in the quality of technical and tactical actions is a good jump.